2020
DOI: 10.1101/2020.04.20.20065979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Liver transplantation without graft ischemia in humans

Abstract: BACKGROUND Ischemia-reperfusion injury is considered an inevitable event that compromises posttransplant outcomes. Numerous treatments have been proposed to reduce its impact. However, most of them have had limited success, as none of them can completely avoid graft ischemia. METHODS Ischemia-free liver transplantation (IFLT) comprises surgical techniques to enable continuous oxygenated blood supply to brain-dead donor livers during procurement, preservation and implantation using normothermic machine perfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…Proteome analysis also showed that neutrophil‐mediated immunity was enhanced in CLT grafts compared to IFLT grafts. However, we did not find a significantly reduced incidence of allograft rejection in the IFLT group, 16 probably due to the use of powerful immunosuppressive drugs and the limited sample size. Rebecca et al reported that exposure of the liver to IRI may subsequently cause inflammatory responses in other organs, which might lead to multiorgan failure 39 .…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Proteome analysis also showed that neutrophil‐mediated immunity was enhanced in CLT grafts compared to IFLT grafts. However, we did not find a significantly reduced incidence of allograft rejection in the IFLT group, 16 probably due to the use of powerful immunosuppressive drugs and the limited sample size. Rebecca et al reported that exposure of the liver to IRI may subsequently cause inflammatory responses in other organs, which might lead to multiorgan failure 39 .…”
Section: Discussioncontrasting
confidence: 84%
“…The detailed clinical data are described in our recently published paper. 16 There was no significant difference in donor and recipient characteristics between the two groups. IFLT recipients had a lower incidence of early allograft dysfunction, and higher one‐year graft/patient rates than CLT recipients.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Therefore, in highly suitable areas, the introduction of resistant varieties, such as Ruiyu and Jinyan, should be recommended. Additionally, the "technical regulations for comprehensive control of kiwifruit brown spot" [31] formulated by Sichuan Agricultural University should be adopted for the scientific and efficient control of the disease. Consistent with the research conclusion of Cui [32], the incidence and disease index were significantly negatively correlated with altitude; as the altitude increased, they decreased gradually.…”
Section: Discussionmentioning
confidence: 99%